Pen and ink drawing workbook - Dunn, Alphonso (Woodland Park, New Jersey : Three Minds Press, 2018)
"Pen & Ink Drawing Workbook is perfect for anyone looking for a book that provides lots of practice for developing and refining ink drawing skills and technique. It is appropriate for learners on all levels and is filled with over 100 engaging drills and exercises. The exercises in this comprehensive workbook are thoughtfully designed to take you from the essential elements like pen control, line consistency, basic strokes and variations to more advanced concepts such as, blending values, controlling gradations, shading compound forms, and rendering textures. It covers all the major pen and ink shading techniques including cross-hatching, stippling, scribbling, and more. In addition, there are 30 inspiring drawing exercises on a variety of subjects, which allows you to draw right inside the book. This book is the complementary workbook for Pen and Ink Drawing : A Simple Guide. However, it can still be used on its own as a general workbook for refining your skills and helping you to create stunning ink drawings with confidence!"-- Back cover.
-- Introduction -- Strokes Consistency Pen control Basic strokes Stroke variations Identifying variations Distinguishing strokes Identify uses of strokes -- Shading Varying line-weight Cross-contour lines Creating even value 6-step value scale Identifying values 9-step value scale Blending values Rate of gradation Range of gradation; Direction of gradation Revealing planes Line direction and structure Single-value drawing 3-value shading Shading block forms Shading curves surfaces Shading cylinders Shading spherical forms Simple form composition Local value Controlling emphasis Compound forms -- Simulating texture Texture patterns Texture chart Texture contours Texture follows form Shading textures Texture on blocks Texture on cylinders Texture on spheres Texture on organic forms -- Drawing exercises Garlic Scribbled eye Hat Calla Lilly Beetroot Makeup brush Stripped bow Stripped hat Hammer Mushroom Orange Lettuce Spoon Wooden pail Dog Rabbit Tree Lily Boulder Glass jar Braid Toucan Stippled eye Nose Fish Bird Cat Work book House Burger -- Index.
Includes index.
Keywords: Pen drawing -- Technique; Drawing -- Study and teaching